Synthesis and characterization of fully biobased poly(propylene succinate‐ran‐propylene adipate). Analysis of the architecture‐dependent physicochemical behavior. Issue 17 (15th June 2017) - Debuissy, Thibaud; Pollet, Eric; Avérous, Luc
ABSTRACT: Fully biobased aliphatic random poly(1, 3‐propylene succinate‐ran‐1, 3‐propylene adipate) (PPSA) copolyesters with high molar mass were synthesized with different macromolecular architectures based on various succinic acid/adipic acid (SA/AA) molar ratio, by transesterification in melt. Titanium (IV) isopropoxide was used as an effective catalyst. All synthesized copolyesters were fully characterized by different chemical and physicochemical techniques including NMR, size exclusion chromatography, FTIR, wide angle X‐ray scattering, differential scanning calorimetry, and thermogravimetric analysis. The final copolyesters molar compositions were identical to the feed ones. The different sequences based on succinate and adipate segments were randomly distributed along the chains. All the corresponding copolyesters showed an excellent thermal stability with a degradation onset temperature higher than 290 °C, which increased with the adipate content. According to their compositions and architectures, PPSA copolyesters can exhibit or not a crystalline phase, at room temperature. T g of copolyesters decreased with the adipate content due to the decrease in the chains mobility, following the Gordon–Taylor relation. PPSA showed a pseudo eutectic melting behavior characteristic of an isodimorphic character. Finally, PPSA copolyesters were not able to crystallize during the cooling or the second heating run, due to the 1, 3‐propanediol chemical structure, which led to amorphous materials with the exception of the polyester based solely on AA. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2017, 55, 2738–2748 Abstract : Several high molar mass poly(propylene succinate‐ ran ‐butylene succinate) (PPSA) copolyesters were synthesized from renewable resources at different compositions. The different copolyesters exhibited excellent thermal stability. PPSA showed an isodimorphic co‐crystallization behavior with only one crystalline phase according to the succinic acid/adipic acid composition. The crystallization rates are very slow due to 1, 3‐propanediol, leading to mainly amorphous materials after the first melting. Moreover, T g decreased with the adipate content according to the Gordon–Taylor equation.